Analysis of lip prints as a predictive tool in screening Type 2 diabetes mellitus - A cross-sectional study - Vineeth Ramanathan; Jimsha Vannathan Kumaran; Subramanian Vasudevan Srinivasan; Mariappan Jonathan Daniel (Wolters Kluwer Medknow Publications, 2020)
Background: Globally, the prevalence of diabetes is soaring among middle- and low-income countries. Lip print is a noninvasive procedure which is being genetically determined to serve as a tool in forensic dentistry. Hence, the present study was conducted to assess the role of lip prints among Type 2 diabetes mellitus (DM). Aims and Objectives: The aim and objective of the study were to assess the lip pattern of the individual among diabetic and nondiabetic individuals, and the objective was to compare and correlate lip print pattern in patients with Type 2 DM. Materials and Methods: The study was conducted on 25 uncontrolled Type 2 DM patients and 25 healthy controls. Lip prints were obtained and classified using Suzuki and Tsuchihashi's classification. Statistical Analysis: The software SPSS (Statistical Package for the Social Sciences) version 20 was used for statistical analysis. Chi-square test was used for comparison. Results: The results of the present study demonstrated that Type 4 reticular pattern was significantly higher among diabetic patients. Conclusion: The present study showed that lip prints may serve as a predictive tool in screening Type 2 DM.